“A Binding Contract Between the Dominant and the Submissive”: Linguistic Analysis of Gender Bias in Fifty Shades of Grey (2015) - Papada Srithreerawichai; Alisa Lekdam; Yadsamin Muprasit; Pum Chanpom (Journal of Communication in Scientific Inquiry (JCSI), 2024)
Language, a significant tool for communication, is implemented to express an interlocutor’s attitude. Their language choice can imply manipulation of power or discrimination between sexes, also known as sexist language. Since dialogues in movies represent real-world communication, this study aims to delve into the sexist language depicted in Fifty Shades of Grey (2015), a romantic drama film. In particular, the genre reflects the apparent discrepancy between male and female counterparts in terms of language and gender bias. The movie was then selected as the main text for the linguistic investigation of sexist language in this descriptive qualitative research. The essential framework in this research is centered extensively on Sara Mills’ theory regarding language and feminism encompassing overt sexism and indirect sexism. Overt sexism is categorized into six types including generic pronouns, generic nouns, non-parallel terms, sexism in proverbs, sexism in swear word, and derivation. On the other hand, indirect sexism is categorized into six subtypes, namely humor, presupposition, conflicting message, scripts and metaphors, collocation, and androcentric perspective. The researchers observe that characters and their attitudes render sexist ideology while their utterances convey gender-related discrimination.